Rancang Bangun Game Manik Angkeran Berbasis Android Pada Tahap Level Poin Pertama - Pandawana, I Dewa Gede Agung; Putra, I Nyoman Agus Suarya; Yusa, I Made Marthana (INFOTEKS (Information Technology, Computer and Sciences), 2019)
This research is the next stage of the previous research entitled Development of the Awakening Bead Figure for Interactive Game Media The Story of the Separation of Java and Bali Based on Android. A problem where as the times and technology develop, folklore begins to be forgotten. To attract children's interest, an interactive folklore game media was made based on Android. In previous studies, the design of all characters from Manik Angkeran was carried out. Whereas in this advanced research, it will be designed and built level by level from Manik Angkeran Game. Where at each level of the game, Manik Angkeran characters will face different giants. Manik Angkeran must defeat the giants in order to proceed to the next level. Every time you fight a giant, Manik Angkeran will get a gold coin (pis bolong mas). Where later, these coins can be used to buy building materials, which will be used to build a dormitory (pesraman). The final goal of this game is to battle the figure of Manik Angkeran to get the golden Dragon Basukih. The opposing giants of Manik Angkeran are taken from the symbols in the semiotics of images which give an impression of the psychology of human life which includes, greed (Pig), greed and anger (Giant). At the level of this game, what I want to say is that things related to greed, greed and selfishness can be easily defeated